IMPACTO FINANCIERO GENERADO POR LA CALIDAD DEL SERVICIO DE ACUEDUCTO EN EL BARRIO CHIMILA DE LA CIUDAD DE SANTA MARTA, AÑO 2022 - Pedroza Alzate Aura Maria; Acosta Barraza Stefany Vanesa (Universidad Antonio Nariño, 2025)
To identify the financial impact of the families of Barrio Chimila, generated by the quality of the aqueduct service, has been the objective of this monographic research, a topic that is interesting because it is a problem that this community has been suffering for many years, under the indifferent gaze of the governments of the time. For this, we began with the elaboration of a bibliographic search of scientific literature on the subject, followed by an analysis of the information, all this work allowed us to evidence a negative impact in relation to the financial aspect of the families of the Chimila neighborhood of the city of Santa Marta, since these families have to invest a large sum of money every month, This is reflected in a precarious quality of life of the population. Likewise, it was possible to see a great social inequality, which requires actions to solve the problems of this community